Novel Therapeutic Savior for Osteosarcoma: The Endorsement of Ferroptosis - Qiu, Cheng; Liu, Tianyi; Luo, Dan; Luan, Dongyang; Cheng, Lin; Wang, Songgang (Frontiers in Oncology, 2022)
Ferroptosis has recently been discovered as an iron-dependent and non-apoptotic regulated mechanism of cell death. The induction of ferroptosis in tumor cells improves tumor treatment, making it a current research hotspot. Mechanistically, it starts by lipid peroxidation, iron accumulation, reactive oxygen species (ROS) production, and glutathione deprivation, highlighting novel treatment opportunities for many tumors and neurodegenerative disorders. Several tumor cell lines are resistant to ferroptosis inducers, even when the ferroptosis key enzyme glutathione peroxidase 4 (GPX4) is blocked, indicating that other important elements are also involved in this process. Ferroptosis-suppressor-protein 1 (FSP1) was discovered to be one of these elements in addition to a few others such as ferroptotic gatekeepers like GTP cyclohydrolase 1 (GCH1) and dihydroorotate dehydrogenase (DHODH). Osteosarcoma is the most common primary malignant bone tumor observed most frequently in children and adolescents. Several studies demonstrated that ferroptosis plays a critical role in the treatment of osteosarcoma, in particular drug-resistant osteosarcoma cells. We outlined four primary regulators involved in ferroptosis in this article, reviewed previously published studies of ferroptosis in osteosarcoma to provide covert insights about osteosarcoma treatment, and highlighted several critical issues to point out future research possibilities.